Two Broad Host Range Rhizobial Strains Isolated From Relict Legumes Have Various Complementary Effects on Symbiotic Parameters of Co-inoculated Plants - Safronova, Vera; Belimov, Andrey; Sazanova, Anna; Chirak, Elizaveta; Kuznetsova, Irina; Andronov, Evgeny; Pinaev, Alexander; Tsyganova, Anna; Seliverstova, Elena; Kitaeva, Anna; Tsyganov, Viktor; Tikhonovich, Igor (Frontiers in Microbiology, 2019)
Two bacterial strains Ach-343 and Opo-235 were isolated respectively from nodules of Miocene-Pliocene relict legumes Astragalus chorinensis Bunge and Oxytropis popoviana Peschkova originated from Buryatia (Baikal Lake region, Russia). For identification of these strains the sequencing of 16S rRNA (rrs) gene was used. Strain Opo-235 belonged to the species Mesorhizobium japonicum, while the strain Ach-343 was identified as M. kowhaii (100 and 99.9% rrs similarity with the type strains MAFF 303099T and ICMP 19512T, respectively). Symbiotic genes of these strains as well as some genes that promote plant growth (acdS, gibberellin- and auxin-synthesis related genes) were searched throughout the whole genome sequences. The sets of plant growth-promoting genes found were almost identical in both strains, whereas the sets of symbiotic genes were different and complemented each other with several nod, nif and fix genes. Effects of mono- and co-inoculation of Astragalus sericeocanus, Oxytropis caespitosa, Glycyrrhiza uralensis, Medicago sativa and Trifolium pratense plants with the strains M. kowhaii Ach-343 and M. japonicum Opo-235 expressing fluorescent proteins mCherry (red) and EGFP (green) were studied in the gnotobiotic plant nodulation assay. It was shown that both strains had a wide range of host specificity, including species of different legume genera from two tribes (Galegeae and Trifoliea). The effects co-microsymbionts on plants depended on the plant species and varied from decrease, no effect, to increase in the number of nodules, nitrogen fixing activity and plant biomass. This phenomenon can be explained by the complementarity of symbiotic genes in the co-microsymbionts which responsible for the specific modification of Nod-factors and nitrogenase activity. Localization and co-localization of the strains in nodules was confirmed by the confocal microscopy. Analysis of histological and ultrastructural organization of A. chorinensis and O. popoviana root nodules was performed. It can be concluded that the strains M. kowhaii Ach-343 and M. japonicum Opo-235 demonstrate lack of high symbiotic specificity that is characteristic for primitive legume-rhizobia systems. Further study of the root nodule bacteria having complementary sets of symbiotic genes will contribute to clarify the evolutionary paths of legume-rhizobia relationships and the mechanisms of effective integration between partners.